Robotic Arm-Assisted Total Knee Arthroplasty in the Setting of Combined Extra-articular Deformities of the Femur and Tibia - Sharma Cook-Richardson; Rasesh Desai (Case Reports in Orthopedics)
In this case, we will describe a 68-year-old man with combined femoral and tibial bone deformities who underwent robotic arm-assisted total knee arthroplasty (RATKA) to treat his severe osteoarthritis in the setting of extra-articular deformities that altered the native anatomical axis and the kinematics of the deformed extra-articular bony structures which chronically generated a neomechanical axis. The combination of severe osteoarthritis with extra-articular deformities made the RATKA method the best surgical treatment option taking into account altered kinematics of the native joint which conventional jig-based total knee arthroplasty would not have prioritized during bony cuts and implant positioning. The patient underwent successful knee arthroplasty with robotic arm-assisted technology with restoration of the mechanical axis.